A short catechism of Christian doctrine and hymns [electronic resource] - Stewart, Samuel Milliken, 1865-1954. (London : Society for Promoting Christian Knowledge, 1914)
In syllabic characters with captions in English. "For the use of the Eskimo in Ungava." Electronic reproduction. Mode of access: Internet. 44